2020
DOI: 10.3390/ijerph17197265
|View full text |Cite
|
Sign up to set email alerts
|

Medical Fraud and Abuse Detection System Based on Machine Learning

Abstract: It is estimated that approximately 10% of healthcare system expenditures are wasted due to medical fraud and abuse. In the medical area, the combination of thousands of drugs and diseases make the supervision of health care more difficult. To quantify the disease–drug relationship into relationship score and do anomaly detection based on this relationship score and other features, we proposed a neural network with fully connected layers and sparse convolution. We introduced a focal-loss function to adapt to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…In [14], the fraud detection model is proposed and disease-drug based relationship is used to identify outliers. The k-means and isolation forest algorithms are used on different datasets and it is identified that isolation forests perform better than k-means clustering for the model.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In [14], the fraud detection model is proposed and disease-drug based relationship is used to identify outliers. The k-means and isolation forest algorithms are used on different datasets and it is identified that isolation forests perform better than k-means clustering for the model.…”
Section: Background and Related Workmentioning
confidence: 99%
“…An anomaly detection technique was used to measure the likelihood of fraudulent health insurance claims records based on historical claims (Kirlidog & Asuk, 2012). Another study (Zhang et al, 2020) detected anomalies by quantifying disease-drug relationships in association scores and other features with a neural network with fully connected layers and infrequent convolutions.The study introduced focal-loss function to adapt to unbalanced data as well as relative probability scores to measure model performance. In another study (Herland et al, 2019), random under sampling (RUS) and SMOTE were applied to deal with imbalance data.…”
Section: Related Workmentioning
confidence: 99%
“…In Reference [47] the authors deploy a one‐class classification algorithm to identify the products' quality abnormalities through the analysis of manufacturing, inspection and after‐sales service data. While in Reference [48], medical frauds and abuses are detected using different clustering‐based algorithms, that is, DBSCAN, LOF, Isolation Forest, and K‐means. Because of the sensitivity of medical data, anomaly detection plays a major role in preserving the privacy of the patients.…”
Section: Related Workmentioning
confidence: 99%